PEMGEMBANGAN MULTIMEDIA PEMBELAJARAN INTERAKTIF TERINTERGRASI EVALUASI PADA MATA PELAJARAN INFORMATIKA KELAS VIII SMP KRISTEN MAKALE - Murni Melati Putri; Muh.Putra Pratama; Ervianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was conducted at Makale Christian Junior High School. The purpose of this study is to describe the needs of interactive learning multimedia development, interactive multimedia development design, and the validity and practicality of interactive learning multimedia. This research uses the research method (Resarch and Development). The results of the problem findings found that the use of learning media is still not optimized while facilities such as internet connections are sufficient. The results of this study are (1). The form of presentation of material in multimedia is designed to be tailored to the learning objectives, (2) the design of interactive learning multimedia development in the form of geogle slide presentations in which there are interactive elements such as learning videos and interactive quizzes. (3) This interactive learning multimedia is included in the "valid" category with a percentage value of 68.23% from media experts, and 88% in the "very valid" category in the assessment of material experts and integrated interactive learning multimedia evaluation is included in the category of "very practical" based on the teacher's practicality assessment of 80%, and the practicality assessment by students 92.69%, so that this integrated interactive multimedia defense evaluation is declared very practical to use in Learning.